1985
DOI: 10.1159/000180069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Hormone-Releasing Factor on Plasma Growth Hormone, Prolactin and Somatomedin C in Hypopituitary and Short Normal Children

Abstract: We studied the effect of a single intravenous bolus of 0.5 µg/kg of growth hormone-releasing factor (GRF) on plasma GH, prolactin (PRL) and somatomedin C (SMC) in 12 short normal children and 24 patients with severe GH deficiency (GHD), i.e. GH < 5 ng/ml after insulin and glucagon tolerance tests. GRF elicited an increase in plasma GH in both short normal and GHD children. The mean GH peak was lower in the GHD than in the short normal children (8.2 ± 2.5 vs. 39.2 ± 5.1 ng/ml, p < 0.001). In the GHD patients (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…In this study we found no temporary increase in prolactin after GHRH injection (2 pg/kg). This con trasts with the findings of other investiga tors, who have found a dose-dependent in crease in prolactin levels after GHRH [18,19]. No other hypophyseal hormone was found to be affected by GHRH in this study.…”
Section: Arginine-insulin Testsupporting
confidence: 90%
“…In this study we found no temporary increase in prolactin after GHRH injection (2 pg/kg). This con trasts with the findings of other investiga tors, who have found a dose-dependent in crease in prolactin levels after GHRH [18,19]. No other hypophyseal hormone was found to be affected by GHRH in this study.…”
Section: Arginine-insulin Testsupporting
confidence: 90%
“…GH is the strongest secretagogue for IGF I, which is synthesized in several organs including the kid neys and liver [10], GH-deficient subjects are also defi cient in IGF I and II. The plasma IGF I levels in these individuals are often below the detection limit of com mercially available radioimmunoassays [11]. Plasma IGF levels start to rise about 8-16 h after a single GH injection.…”
mentioning
confidence: 98%
“…The negative correlations between the GH peak after GHRH and the chronological [15]or bone ages [16]in children with GH deficiency have been previously reported, but not in normal children. We found a higher GH response in patients aged less than 5 years than in the oldest, as recently reported [2].…”
Section: Discussionmentioning
confidence: 98%